Medical cell technologies for treatment of patients suffering from recessive dystrophic epidermolysis bullosa. Method of intracutaneous administration of fibroblasts - V. I. Albanova; A. E. Karamova; V. V. Chikin; A. A. Mineyeva (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Recessive dystrophic epidermolysis bullosa (RDEB) is a severe inherited disease developing due to genetic abnormalities in the synthesis of Type VII collagen by fibroblasts. A low production rate of Type VII collagen and abnormalities related to the formation of anchoring fibrils weaken the epidermis and derma adhesion strength, which results in the formation of blisters or erosions in case of any mechanical injury. Fibroblasts and keratinocytes belong to the key sources of Type VII collagen in the skin. Application of allogeneic fibroblasts is a promising cell technique for treating RDEB patients. The therapeutic effect of fibroblasts intradermal administration is stipulated by high stability of newly synthesized Type VII collagen and its ability to form anchoring fibrils in the area of the dermoepidermal junction. According to experimental and clinical studies, it is possible to boost the content of Type VII collagen in the dermoepidermal junction area and heal long-term skin defects in RDEB patients by means of intradermal administration of allogeneic fibroblasts.